Monocyte/macrophages and their role in HIV neuropathogenesis. Issue 1 (16th June 2013) - Burdo, Tricia H.; Lackner, Andrew; Williams, Kenneth C.
Summary: Neurological sequelae of human immunodeficiency virus (HIV) infection have been and remain a significant problem. Monocytes and macrophages in humans and monkeys are susceptible to infection by HIV and simian immunodeficiency virus (SIV), and are considered to be a main mechanism by which the central nervous system (CNS) is infected. Within the infected CNS, perivascular macrophages and, in some cases, parenchymal microglia are infected as are multinucleated giant cells when present. While neurons are not themselves directly infected, neuronal damage occurs within the infected CNS. Despite the success of antiretroviral therapy (ART) in limiting virus in plasma to non‐detectable levels, neurological deficits persist. This review discusses the continued neurological dysfunctions that persist in the era of ART, focusing on the roles of monocyte and macrophage as targets of continued viral infection and as agents of pathogenesis in what appears to be emergent macrophage‐mediated disease resulting from long‐term HIV infection of the host. Data discussed include the biology of monocyte/macrophage activation with HIV and SIV infection, traffic of cells into and out of the CNS with infection, macrophage‐associated biomarkers of CNS and cardiac disease, the role of antiretroviral therapy on these cells and CNS disease, as well as the need for effective adjunctive therapies targeting monocytes and macrophages.